Editorial 7.2 - O'Reilly, Dr Meg (Journal of University Teaching and Learning Practice, 2010)
Welcome to Volume 7, Issue 2 of JUTLP. It is wonderful to see the journal continuing from strength to strength, and with this Special Issue devoted to the theme of “Achieving Teaching-Research Connections in Undergraduate Programs”, there was an enormous response from authors in Australia, New Zealand and the UK. Although we have stretched the issue to encompass more articles than usual, there were simply too many well-conceived initiatives to include them all in this issue. Watch out for extra articles on this theme in future issues.